Biodiversitas Avifauna dan Insekta Sebagai Bioindikator Keasrian Kampus UIN Alauddin Makassar - A. Ridha, Ariati; Yunadia; Amrullah, Syarif Hidayat; Alir, Rahmat Fajrin; Nurman, Nurman (Department of Biology Education of Universitas Islam Negeri Alauddin Makassar, 2024)
The presence of avifauna and insects provides ecological value and contributes significantly to the sustainability and well-being of the academic community. By maintaining biodiversity, the UIN Alauddin Makassar campus can serve as a model for other educational institutions while fulfilling one of the Chancellor's Pancacita goals: creating a campus that is academically excellent and environmentally friendly. This study aimed to examine the diversity of avifauna and insects as bioindicators on the UIN Alauddin Makassar Campus using the Index Point of Abundance (IPA), with samples taken at 5 points on Campus 1 and 10 points on Campus 2. The results revealed 28 avifauna species, with 192 individuals in Area A and 605 individuals in Area B, where Passer montanus had the highest abundance (218 individuals). Insect diversity included 106 species, with 564 individuals in Area A and 694 in Area B. The most abundant insect in Area A was Solenopsis invicta (fire ants, 65 individuals), while Oecophylla smaragdina (weaver ants, 146 individuals) dominated in Area B. The diversity of avifauna and insects serves as a bio-indicator of environmental health, meaning a good habitat quality and supporting a balanced ecosystem. The findings suggest that the UIN Alauddin Makassar Campus remains relatively pristine and aesthetically pleasing, supported by the high number of species and ecological indices observed.